The COVID-19 pandemic and firms’ E-learning use : implications for inequality in training opportunities - Müller, Christoph [Verfasser] (My University, 2024)
„This paper investigates whether the adoption of E-learning by firms contributed to offset the decrease in firm-sponsored training during the COVID-19 pandemic. Using a novel firm level survey linked with administrative data on the universe of workers within those firms, I study the role of E-learning in firms’ training activities during the crisis. I find that the COVID-19 pandemic substantially decreased firm-sponsored training by up to 11 percentage points. However, firms’ ability to use E-learning nullifies this negative effect. Furthermore, the differential capabilities of firms to apply E-learning might exacerbate already prevalent inequalities in training opportunities.“ (author’s abstract; BIBB-Doku)
Keywords: S 3.2 Unternehmen und Behörden; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; L 4.2.3 Internetbasiertes Lernen / E-Learning; 370; Pandemie; Betrieb; Betriebliche Weiterbildung; Weiterbildungsbeteiligung; E-Learning; Einflussfaktor